Test of Receivability and Fiber Concerning of Talam Cake with The Addition of Chia Seed Flour Techikade as Snack for Constipation - Yanfa' Qurrota 'Ayun Sari; Ani Intiyati; Mujayanto (Journal of Nutrition Explorations, 2023)
Constipation (constipation) can occur at any age. One of them is stomach cramps. The purpose of this study was to determine the acceptability and fiber content of the platter cake with the addition of chia seed flour and soybean flour as a snack for constipation. The method of this study was an experiment on 3 formulations of the addition of rice flour, chia seed flour and soybean flour with the formulations KT1 (110:65:25), KT2 (100:75:25), and KT3 (90:80:30). ), using the organoleptic preference test in the form of likes or dislikes for the color, taste, aroma and texture of the Techikade platter cake presented to 25 panelists, the fiber content of the Techikade platter cake used the Gravimetric Method for the best formulation of the organoleptic test results. The results showed that the platter cake with the KT3 formulation was the most preferred with an average score of 3.76 which was included in the like category. The conclusion of the study showed organo-leptic properties, the formulation favored by the panelists was the KT3 formulation with a ratio of rice flour:chia seed flour:soy flour of 90:80:30 having a fiber content of 5.64% in 100g Techikade tray cake.